Synthesis and antimicrobial activity of 1-(5-Mercapto-1,3,4-Oxadiazol-2-yl) -2-(Pyridine-2-ylamino)ethanone - Jumat Salimon; Nadia Salih; Hasan Hussien (Universiti Kebangsaan Malaysia, 2011)
1-(5-Mercapto-1,3,4-oxadiazol-2-yl)-2-(pyridine-2-ylamino)ethanone (3), has been synthesized from 2-(pyridine-2-ylamino)acetohydrazide (2). A yellow colored compound (2) was reacted with carbon disulfide and potassium hydroxide in absolute ethanol to obtain the 1-(5-mercapto-1,3,4-oxadiazol-2-yl)-2-(pyridine-2-ylamino)ethanone. Structures of the synthesized compounds were supported by means of IR, NMR, MS spectroscopic and elemental analysis. The synthesized compounds were evaluated for their antimicrobial activity and were expressed as the corresponding minimum inhibitory concentration (MIC). A brown colored compound (3) with 90% yield has been successfully synthesized. This compound was found to have significant antimicrobial activity with MIC value ranging from 30.2 - 43.2 μg cm-3. The findings of the present study indicate that cyclization of hydrazide acid group of 2-(pyridine-2-ylamino)acetohydrazide (2) into 1,3,4-oxadiazole nucleus resulted in increased antimicrobial activity.